Abscess resulting from Mycobacterium kansasiiin the left thigh of AIDS patient - Catarina Tenório de Lima; Vera Magalhães (Sociedade Brasileira de Dermatologia, 2014)
A case of abscess resulting from Mycobacterium kansasii, in the left thigh of a 53-year-old woman infected with the Human Immunodeficiency virus, is reported. Curiously, there was no pulmonary or systemic involvement as is usual with these Mycobacterium infections. The patient had CD4 T lymphocyte count of 257 cells/µL and a viral load of 60,154 copies. Despite presenting a relatively preserved immunity, the patient also presented Criptococcic meningoencephalitis and Esophageal candidiasis. The patient responded satisfactorily to treatment for infections and after 51 days was discharged.